PERAN NILAI BUDAYA SUNDA DALAM POLA ASUH ORANG TUA BAGI PEMBENTUKAN KARAKTER SOSIAL ANAK (Studi Deskriptif di Desa Suntenjaya Kec. Lembang Kab. Bandung Barat) - al Madjid, Muhamad Aqros Syaiful Ridho V (International Journal Pedagogy of Social Studies, 2016)
Abstract--It is undeniable that at this point Sundanese culture was being shifted due to the development of globalization. Many sundanese values are displaced or even weakened. Parents provide upbringing with sundanese value so that children will have decent characters and will have affected the social behavior in them. Ekadjati stated that Sundanese culture is a culture which lives, grows and develops within Sundanese people who generally live in West Java. According to Thoha, parenting itself is a great way adopted by parents in teaching their child which is seen as an act of taking responsibility upon the children. Besides Sundanese culture and Parenting, the character building which has been done by parents to the favor of their children is not only to guide and foster the intellectual competence and mechanical skills of each child but also focused in achieving the character growth and development.Keywords: Sundanese cultural values, Parenting and Character Building